Gravity anomalies and segmentation at the East Coast, USA continental margin - Wyer, P; Watts, A (2006)
The free-air gravity 'edge effect' anomaly at rifted continental margins has generally been attributed to the transition between thick continental and thin oceanic crust. While crustal thinning is a major contributor, recent studies suggest that sediment loading and magmatism may significantly modify the edge effect anomaly and cause it, at some margins, to be highly segmented along their strike. In this paper, we use a combined 3-D flexural backstripping and gravity anomaly modelling technique to determine the role that sediment loading has played in controlling the segmentation of Atlantic-type continental margins. We focus on the East Coast, USA since a substantial amount of high-quality seismic reflection and refraction, gravity, and magnetic data already exists for this margin. By calculating the gravity anomaly associated with rifting and sediment loading and iteratively comparing it to the observed free-air anomaly, we have determined the 'best-fit' elastic thickness, Te, structure of the margin. We show that 0 < Te < 40 km and that Te varies across-strike and along-strike the margin. Since Te is a proxy for the long-term (>105 a) integrated strength of the lithosphere, these results imply that weak regions abut strong ones at the East Coast, USA margin. Te generally decreases with increase in the amounts of crustal thinning, β, and the flexed basement curvature, K, suggesting it is controlled, at least in part, by the mechanical structure of the pre-rift lithosphere and yielding due to flexural loading. However, there is considerable scatter, suggesting other factors such as along-strike changes in crustal composition. Irrespective, we show that an isostatic anomaly that takes into account the 'best-fit' Te distribution is significantly reduced in spectral power compared with one which is computed assuming only Airy compensation (i.e. Te = 0 km). This is not to imply that rifting and sediment loading completely accounts for the anomalies along-strike and across-strike the East Coast, USA margin. To the contrary, significant isostatic anomaly highs and lows persist, especially in inner and middle shelf regions. One of the most prominent is an arcuate, 670 km long, high with flanking lows offshore Carolina that we attribute to magmatism during the initial stages of continental break-up. © 2006 The Authors Journal compilation © 2006 RAS.